Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]f(x)=2x^2+2x-3\\y=2x^2+2x-3\\a=2, b=2, c=-3[/tex]
Postać kanoniczna: [tex]y=a(x-p)^2+q[/tex] , gdzie:
[tex]p=\frac{-b}{2a}\\\\q=\frac{-\Delta}{4a}[/tex]
[tex]p=\frac{-2}{2*2}=-\frac{2}{4}=-\frac{1}{2}[/tex]
[tex]q=\frac{-\Delta}{4a}=\frac{-(b^2-4ac)}{4a}=\frac{-(2^2-4*2*(-3))}{4*2}=\frac{-(4+24)}{8}=-\frac{28}{8}=-\frac{7}{2}=-3\frac{1}{2}[/tex]
Zatem postać kanoniczna to: [tex]y=2(x-(-\frac{1}{2}))^2-3\frac{1}{2}=2(x+\frac{1}{2})^2-3\frac{1}{2}=2(x+\frac{1}{2})^2-\frac{7}{2}[/tex]